Radiographic features of Kirner's deformity. (10th June 2013) - Satake, Hiroshi; Ogino, Toshihiko; Eto, Jun; Maruyama, Masahiro; Watanabe, Tadayoshi; Takagi, Michiaki
Abstract We conducted a study of Kirner's deformity to investigate its radiologic features and consider its possible causes. Sixty‐seven patients with Kirner's deformity, 41 in our series and 26 retrieved in a survey of the literature were investigated. We divided Kirner's deformity into three types according to the site of curvature: the epiphyseal line, diaphysis, and distal tip. Among our series, 12 hands were affected in males and 26 in females. The gender of the patients for the other three hands was unknown. Twelve cases occurred on the right side, five on the left side, and 24 on both sides. Radiographic data for 34 hands were available. The palmar surface of the distal phalanx was at a mean angle of 27.4 degrees to the long axis of the middle phalanx. Epiphyseal line curvature was seen in four hands (mean patient age, 11 years), diaphysis curvature in 10 (mean age, 12.4 years), and distal tip curvature in 20 (mean age, 26.5 years). Dorsal subluxation of the distal phalanx was noticed in six hands (18%). Radiographic data for 26 hands reported previously were analyzable. The differences between epiphyseal line or diaphysis curvature and distal tip curvature in terms of age were significant in both the present study and the literature.